2018
DOI: 10.1016/j.jisp.2017.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Alopecia Areata with Simvastatin/Ezetimibe

Abstract: Alopecia areata (AA) is an autoimmune disorder characterized by T lymphocytic infiltrates around the bulbar region of hair follicles. Statins have surfaced as potential therapeutic agents for AA, partly because of their modulation of the JAK/STAT pathway. Some data indicate that statins are a possible option for acute, but not chronic, longstanding AA. Animal studies suggest that treatment with statins increases CD4/CD25/Foxp3 populations in AA-affected mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…It should be stated that this case study was not a randomised control trial and care should be taken in interpreting these observations, considering the potential for spontaneous regrowth in this disorder. Indeed, the extent of regrowth in response to this therapy varies significantly between studies, ranging from <20% to ‘significant’, with patients displaying more severe AA receiving no benefit …”
Section: Modulation Of Cholesterol Homeostasis In the Hfmentioning
confidence: 99%
See 3 more Smart Citations
“…It should be stated that this case study was not a randomised control trial and care should be taken in interpreting these observations, considering the potential for spontaneous regrowth in this disorder. Indeed, the extent of regrowth in response to this therapy varies significantly between studies, ranging from <20% to ‘significant’, with patients displaying more severe AA receiving no benefit …”
Section: Modulation Of Cholesterol Homeostasis In the Hfmentioning
confidence: 99%
“…In addition, JAK/STAT inhibitors have proven useful in restoring hair growth in AA patients, by attenuating production of inflammatory cytokines (IL‐2, IL‐15 and interferon‐γ) by cytotoxic T lymphocytes . It is likely that, as seen with JAK/STAT inhibitors, statin‐mediated inhibition of inflammatory cytokine signalling is a mechanism by which statins can help treat acute episodes of AA …”
Section: Modulation Of Cholesterol Homeostasis In the Hfmentioning
confidence: 99%
See 2 more Smart Citations
“…Topical statins represent a promising new therapeutic approach for the treatment of chronic wounds, and several studies have shown that statins exert beneficial pleiotropic effects extending beyond reducing systemic cholesterol levels. These include antiinflammatory, antibacterial, anticancer, and improved endothelial function, suggesting that statins may have beneficial effects in the treatment of various diseases (7)(8)(9)(10)(11)(12)(13)(14). In addition, statins are currently recommended as a standard of care therapy for DM, and systemic statin use has been shown to correlate with increased wound healing in patients with chronic wounds (8,15,16).…”
Section: Introductionmentioning
confidence: 99%